Business Planning : Sweet Corn Enterprise / Mariah Mohd Jizi ...[et al.] - Mohd Jizi, Mariah; Awang Yak, Noorazreen Laily; Nik Hassan, Nik Harizah; Mohd Ripan, Nor Asma (2009)
Name of our business is “Sweet Corn Enterprise”. The concepts of our business are to grow and export corn in the world wide marketing. It is cover in an outside Malaysia’s market. We will come out the good quality of corn from various techniques in biotechnology. The farm is located in strategic location on Pasir Mas, Kelantan. This location has healthy land to grow the corn widely. Another factor that is contributed we choose this location because it is nearest with the agro institution, (KADA). This business is also one of the projects under KADA. The business is started on 10th February 2008, because that time we already have training and get supporting by KADA like utilities and financial. Other briefs, environmental factor suitable to grow the corn